Two new Keggin-type polyoxometalate-based organic-inorganic hybrid compounds with metal ions and chelate ligands. Issue 7 (3rd April 2017) - Jia, Shi-Fang; Hao, Xiu-Li; Ma, Yuan-Yuan; Wang, Hong-Yi; Li, Yang-Guang
Abstract: Two new hybrid compounds with chemical formulas [Co(L1 )2 (H2 O)2 ]2 [SiW12 O40 ]·6H2 O (1 ) and [Cu2 (C9 H22 N)2 (L2 )2 ][SiW12 O40 ]·2H2 O (2 ) (L1 = 3, 3′-diamino-5, 5′-bis(1H-1, 2, 4-triazole), L2 = 1, 2-bis(3-(2-pyridyl)pyrazole-1-ylmethyl)benzene, C9 H22 N = tripropylamine) were prepared in a hydrothermal reaction system containing Keggin-type polyoxometalates (POMs), transition metal (TM) salts (cobalt salts and copper salts), and chelate L1 /L2 ligands. X-ray structural analysis reveals that1 and2 possess 3-D supramolecular host frameworks with large cavities and the polyoxoanions SiW12 reside in these cavities as the guest templates. The photocatalytic activities of1 and2 were investigated. Both compounds show efficient catalytic activity for degradation of RhB with1 > 2 . The loading amount of the POM units and the structural features of these POM-based organic-inorganic hybrid compounds may be necessary factors that affect the activity of catalysts in the photocatalytic degradation. Abstract :